キングジョージ トウ ノ 2 シュ ヨリ ナル センルイ コロニー ノ コウゾウ ニ ツイテ - 中坪, 孝之; ナカツボ, タカユキ; 大谷, 修司; オオタニ, シュウジ; Nakatsubo, Takayuki; Ohtani, Shuji (1992)
P(論文) キングジョージ島の長城基地周辺において, 蘚類Sanionia uncinataとBryum pseudotriquetrumで構成されるコロニーの縦断面を観察し, コロニー内における2種の関係と, そのコロニーの構造に及ぼす影響を調べた。その結果, B. pseudotriquetrumのシュートから成る層がS. uncinataのシュートで部分的に被われている場合, 逆にS. uncinataのシュートの層がB. pseudotriquetrumのシュートで部分的に被われている場合, 両種が互いに被いあうことなく共存している場合の3パターンが認められた。コロニーの成長にともない, 2種の割合は徐々に変化するが, その変化の方向は生育地の中でも一定ではないことが明らかになった。 Moss colonies composed of two species Sanionia uncinata and Bryum pseudotriquetrum are abundant in the vicinity of Great Wall Station on King George Island. Vertical cross-sections of these colonies were examined to know the colony structure indicating the interaction between the two species. In several colonies, a layer composed of B. pseudotriquetrum was partially covered with shoots of S. uncinata (pattern 1). In some other colonies, a layer composed of S. uncinata was partially covered with shoots of B. pseudotriquetrum (pattern 2). For the rest of the colonies, both species coexisted without covering each other (pattern 3). It is concluded that the proportion of the two species in a colony has changed through the colony growth, but the direction of the change varies among the colonies at each site. departmental bulletin paper